2014
DOI: 10.1016/j.marpolbul.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of polychlorinated biphenyls in the Daliao River estuary of Liaodong Bay, Bohai Sea (China)

Abstract: a b s t r a c tThe distributions of 41 polychlorinated biphenyls (PCBs) were determined in the aqueous phase, suspended particulate matter (SPM), and sediment of the Daliao River estuary in Liaodong Bay, Bohai Sea (China). The total PCB concentrations ranged from 5.51 to 40.28 ng L À1 in the surface water, from 6.78to 66.55 ng L À1 dry weight in the SPM, and from 0.83 to 7.29 ng g À1 dry weight in the sediment. The PCB concentrations in water, SPM, and sediment were moderate relative to those reported for othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…PCB concentrations in the present study were similar to those found in the Ravi River, Pakistan (2.7-202.3 ng g -1 dw) (Iwegbue, 2016), Liaohe River, China (24-158 ng g -1 dw) (Dragan et al, 2006), Bahlui River, Romania (4.9-179.6 ng g -1 dw) (Lv et al, 2015) and Forcados River, Nigeria (4.6-424.3 ng g -1 dw) (Syed et al, 2014). The concentrations were higher than those reported in the Daliao River estuary, China (0.8-7.3 ng g -1 dw) (Men et al, 2014), Chenab River, Pakistan (0.8-59.4 ng g -1 dw) (Mahmood et al, 2014), Durance River, France (0.03-13.3 ng g -1 dw) (Kanzari et al, 2015) and Tonghui River, China (0.8-8.5 ng g -1 dw) (Zhang et al, 2004), but slightly lower than those recorded in the Yellow River, China (nd-700 ng g -1 dw) (Su et al, 2018) and industrialized urban river, France (2.8-435.0 ng g -1 dw) (Kanzari et al, 2014) (Table S11).…”
Section: Distribution and Sources Of Pcbscontrasting
confidence: 75%
See 1 more Smart Citation
“…PCB concentrations in the present study were similar to those found in the Ravi River, Pakistan (2.7-202.3 ng g -1 dw) (Iwegbue, 2016), Liaohe River, China (24-158 ng g -1 dw) (Dragan et al, 2006), Bahlui River, Romania (4.9-179.6 ng g -1 dw) (Lv et al, 2015) and Forcados River, Nigeria (4.6-424.3 ng g -1 dw) (Syed et al, 2014). The concentrations were higher than those reported in the Daliao River estuary, China (0.8-7.3 ng g -1 dw) (Men et al, 2014), Chenab River, Pakistan (0.8-59.4 ng g -1 dw) (Mahmood et al, 2014), Durance River, France (0.03-13.3 ng g -1 dw) (Kanzari et al, 2015) and Tonghui River, China (0.8-8.5 ng g -1 dw) (Zhang et al, 2004), but slightly lower than those recorded in the Yellow River, China (nd-700 ng g -1 dw) (Su et al, 2018) and industrialized urban river, France (2.8-435.0 ng g -1 dw) (Kanzari et al, 2014) (Table S11).…”
Section: Distribution and Sources Of Pcbscontrasting
confidence: 75%
“…Their presence in rural sites such as T1-T3 and M1-M3, however, are probably due to inputs into the river by atmospheric deposition, directly or followed by runoff, given that no local sources of PCBs in these sites. In fact, these congeners exhibit higher mobility in the atmosphere and aquatic environment (Men et al, 2014). The presence of higher-chlorinated PCBs (Hepta-to Nona-CBs, mean of 13.0%) may be due to the discharge of untreated contaminants near the source (Hong et al, 2005).…”
Section: Distribution and Sources Of Pcbsmentioning
confidence: 99%
“…Previous studies have reported the PCB levels in surface sediments from other bays and estuaries around the world ( Table 1). The PCB levels in Qingduizi Bay were generally far below those of more developed industrial estuaries and bays in China, such as Shantou Bay (Shi et al, 2016), three typical bays (Yueqing Bay, Xiangshan Bay, and Sanmen Bay) in the east China Sea (Yang et al, 2011), the Yangtze Estuary (Gao et al, 2013) and the Shuangtaizi Estuary (Yuan et al, 2015); and in other areas of the world, such as Casco Bay in the United States (Kennicutt et al, 1994), Rhone Prodelta in France (Tolosa et al, 1995) and Bizerte lagoon in Tunisia (Barhoumi et al, 2014), yet comparable to the PCB levels in the Daliao Estuary (China) (Men et al, 2014) and Guaratuba Bay (Brazil) (Combi et al, 2013).…”
Section: Occurrence Of Pcbsmentioning
confidence: 89%
“…The Daliao River watershed includes some of the traditional industrial hot spots of China and has been long affected by heavy industries, including chemical/petrochemical, steel-iron and machinery. It was reported that the Daliao River received about 60% of the pollutant discharge load of the entire Liao River watershed (Men et al, 2014). A large amount of pollutants ends up in the Daliao River and is transported into the estuary.…”
Section: Description Of Study Area and Monitoring Campaignmentioning
confidence: 99%